(untitled) (Lex localis - Journal of Local Self-Government, 2019)
It is often assumed that women’s descriptive representation is higher at the local level than at the state or federal level. However, recent studies challenge this perceived pattern. Therefore, several alternative patterns of inter-level gender gaps in female representation across political levels are systematically introduced. Zooming in on the state-local gender gap, a number of explanations as to why such a gender gap can emerge are hypothesized. And the case of the U.S. is used to illustrate how women sometimes fare relatively better at state than local election.